The Structures of Meaningful Life Stories - Owen Flanagan (Gerais, 2008)
Life’s meaning is a matter of how we live in this life. Whatever meaning a life has for the creature whose life itis ends when bodily death occurs. When someone dies the meaning of their life is over for them, in first person.But the meaning of a life for others, for those in relation with the dead person, does not end when a person dies.Our lives, be they good or bad, leave effects, ripples – memories – on others who are different because of us,and future generations who will feel the effects of our being – certainly after long enough time, without everknowing that we existed. This is all the meaning we can reasonably expect a human life to have. But manypeople think that this much meaning is not enough, that for life to be truly meaningful there must be somethingthat makes for eternal or transcendent meaning.